2015
DOI: 10.3389/fped.2015.00079
|View full text |Cite
|
Sign up to set email alerts
|

Evans Syndrome in Children: Long-Term Outcome in a Prospective French National Observational Cohort

Abstract: Evans syndrome (ES) is a rare autoimmune disorder whose long-term outcome is not well known. In France, a collaborative pediatric network set up via the National Rare Disease Plan now provides comprehensive clinical data in children with this disease. Patients aged less than 18 years at the initial presentation of autoimmune cytopenia have been prospectively included into a national observational cohort since 2004. The definition of ES was restricted to the simultaneous or sequential association of autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
6
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 36 publications
2
83
6
6
Order By: Relevance
“…Over a 9‐year period and at a region level, the annual incidence of 0.81 cases per 100,000 children under 18 years confirms the rarity of the disease. The patients’ characteristics are consistent with the whole OBS'CEREVANCE cohort, with a shorter follow‐up: 70% of IgG/IgG + C3d DAT, 14% turn into ES, 43% are associated with a known infectious trigger, and 57% are secondary . This study using a registry‐based methodology thereby expands the severity spectrum of the disease and demonstrates a high frequency of its mild forms.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Over a 9‐year period and at a region level, the annual incidence of 0.81 cases per 100,000 children under 18 years confirms the rarity of the disease. The patients’ characteristics are consistent with the whole OBS'CEREVANCE cohort, with a shorter follow‐up: 70% of IgG/IgG + C3d DAT, 14% turn into ES, 43% are associated with a known infectious trigger, and 57% are secondary . This study using a registry‐based methodology thereby expands the severity spectrum of the disease and demonstrates a high frequency of its mild forms.…”
Section: Discussionsupporting
confidence: 68%
“…OBS'CEREVANCE is a national prospective cohort in which children with autoimmune cytopenia have been consecutively included from 2004 from all regional centers, with information on all medical data from birth to last news. It allowed descriptive studies of 265 children with AIHA and 156 children with ES . Thirty to 40 new cases per year of AIHA and AIHA/ES in children and adolescents are thought to occur in France but this incidence is likely underestimated for two main reasons: mainly the most severe forms are referred to hematological teams and the constitution of the cohort is entirely based on the dynamism of the specialists comprising the network, which may vary over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, ES recurrence or death was not observed in cSLE patients suggesting continuous complete remission, contrasting with other pediatric ES cases without associated lupus . Indeed, multicenter studies evaluating childhood cytopenias reported that approximately only one‐third of pediatric ES patients did not have recurrence and 10% of pediatric ES died at the age of 14 years . Furthermore, ES and other autoimmune cytopenias associated with ALPS seem to be a severe disease with poor outcome and increased risk of malignancy .…”
Section: Discussionmentioning
confidence: 95%
“…Some of these patients have already been reported in descriptive studies (Bader-Meunier et al, 2007;Aladjidi et al, 2011Aladjidi et al, , 2015. Patients with a well-defined inherited immune deficiency and those who received simultaneous disease-modifying treatment in the month before rituximab initiation were excluded.…”
Section: Identification Of Patients and Definitionsmentioning
confidence: 99%